Functional significance of intra‐left ventricular vortices on energy efficiency in normal, dilated, and hypertrophied hearts. Issue 4 (24th October 2020) - Sarashina‐Motoi, Miwa; Iwano, Hiroyuki; Motoi, Ko; Ishizaka, Suguru; Chiba, Yasuyuki; Tsujinaga, Shingo; Murayama, Michito; Nakabachi, Masahiro; Yokoyama, Shinobu; Nishino, Hisao; Okada, Kazunori; Kaga, Sanae; et al.
Abstract: Purpose: To investigate the influence of changes in vortices within the left ventricle (LV) on energy efficiency (EE) in normal and diseased hearts. Methods: We performed vector flow mapping echocardiography in 36 normal participants (N), 36 patients with dilated cardiomyopathy (D), and 36 patients with LV hypertrophy (H). The circulation of the main anterior vortex was measured as a parameter of vortex strength. Energy loss (EL) was measured for one cardiac cycle, and EE was calculated as EL divided by stroke work (SW), which represents the loss of kinetic energy per unit of LV external work. Results: Circulation increased in the order of N, H, and D (N: 15 ± 4, D: 19 ± 8, H: 17 ± 6 × 10 −3 m 2 /s; analysis of variance [ANOVA] P  < .01). Conversely, EE increased in the order of N, D, and H (N: 0.22 ± 0.07, D: 0.26 ± 0.16, H: 0.30 ± 0.16 10 −5 J/mm Hg mL m s; ANOVA P = .04), suggesting worst EE in group H. We found a positive correlation between circulation and SW only in group N, and positive correlation between circulation and EE only in diseased groups (D: R = 0.55, P  < .01; H: R = 0.44, P  < .01). Multivariable analyses revealed that circulation was the independent determinant of EE in groups D and H. Conclusions: Enhanced vortices could be associated with effective increase in LV external work in normal hearts. Conversely, they were associated with loss of EE without an optimal increase in external work in failing hearts, regardless of the LV morphology.